Design of precision-aware subthreshold-based MOSFET voltage reference - Mu, Shuzheng (2023)
A new precision-aware subthreshold-based MOSFET voltage reference is presented in this paper. The circuit was implemented TSMC-40 nm process technology. It consumed 9.6 μW at the supply voltage of 1.2 V. In this proposed work, by utilizing subthreshold-based MOSFET instead of bipolar junction transistor (BJT), relatively lower power consumption was obtained in the design while offering comparable precision to that offered by its BJT counterpart. Through the proposed second-order compensation, it achieved the temperature coefficient (T.C.) of 3.0 ppm/°C in the TT corner case and a 200-sample Monte-Carlo T.C. of 12.51 ppm/°C from -40 °C to 90 °C. This shows robust temperature insensitivity. The process sensitivity of Vref without and with trimming was 2.85% and 0.75%, respectively. The power supply rejection (PSR) was 71.65 dB at 100 Hz and 52.54 dB at 10 MHz. The Figure-of-Merit (FOM) for the total variation in output voltage was comparable with representative BJT circuits and better than subthreshold-based MOSFET circuits. Due to low T.C., low process sensitivity, and simplicity of the circuit architecture, the proposed work will be useful for sensor circuits with stringent requirements or other analog circuits that require high precision applications.